Estrogen Receptor α Is Required for Maintaining Baseline Renin Expression. Issue 5 (May 2016) - Lu, Ko-Ting; Keen, Henry L.; Weatherford, Eric T.; Sequeira-Lopez, Maria Luisa S.; Gomez, R. Ariel; Sigmund, Curt D.
Abstract : Enzymatic cleavage of angiotensinogen by renin represents the critical rate-limiting step in the production of angiotensin II, but the mechanisms regulating the initial expression of the renin gene remain incomplete. The purpose of this study is to unravel the molecular mechanism controlling renin expression. We identified a subset of nuclear receptors that exhibited an expression pattern similar to renin by reanalyzing a publicly available microarray data set. Expression of some of these nuclear receptors was similarly regulated as renin in response to physiological cues, which are known to regulate renin. Among these, only estrogen receptor α (ERα) and hepatic nuclear factor α have no known function in regulating renin expression. We determined that ERα is essential for the maintenance of renin expression by transfection of small interfering RNAs targeting Esr1, the gene encoding ERα, in renin-expressing As4.1 cells. We also observed that previously characterized negative regulators of renin expression, Nr2f2 and vitamin D receptor, exhibited elevated expression in response to ERα inhibition. Therefore, we tested whether ERα regulates renin expression through an interaction with Nr2f2 and vitamin D receptor. Renin expression did not return to baseline when we concurrently suppressed both Esr1 and Nr2f2 or Esr1 and vitamin D receptor mRNAs, strongly suggesting that Esr1 regulates renin expression independent of Nr2f2 and vitamin D receptor. ERα directly binds to the hormone response element within the renin enhancer region. We conclude that ERα is a previously unknown regulator of renin that directly binds to the renin enhancer hormone response element sequence and is critical in maintaining renin expression in renin-expressing As4.1 cells. Abstract : Supplemental Digital Content is available in the text.